2013
DOI: 10.2111/rem-d-12-00113.1
|View full text |Cite
|
Sign up to set email alerts
|

Bison Versus Cattle: Are They Ecologically Synonymous?

Abstract: Historically, the plains bison (Bison bison Linnaeus) was the most numerous and influential grazer on the Great Plains. Today 500 000 bison occupy North America among more than 100 000 000 cattle. In an attempt to restore their historical ecological role, bison are translocated onto landscapes previously manipulated for cattle use through water and fence development. We hypothesized that bison would use these landscapes similarly to cattle, thus maintaining homogenous grazing and reducing the restoration poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 47 publications
1
48
0
Order By: Relevance
“…Thus far, restoration ecologists have stressed the importance of fire much more than native ungulate grazing. However, understanding the role of grazers is becoming necessary as bison ( Bos bison L.) or elk ( Cervus elaphus L.) are reintroduced (Knapp et al ; Martin & Wilsey ; Jackson et al ; Kohl et al ), and cattle are used to facilitate establishment of native grasses and forbs in restorations (Bouressa et al ; Allred et al 2011 a ). Although very intense grazing can be detrimental to species diversity, moderate grazing (either in frequency or intensity) could have positive effects on species diversity when the grazing mammals feed on dominant grasses and sedges, especially when grazing is patchy (Allred et al 2011 b ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, restoration ecologists have stressed the importance of fire much more than native ungulate grazing. However, understanding the role of grazers is becoming necessary as bison ( Bos bison L.) or elk ( Cervus elaphus L.) are reintroduced (Knapp et al ; Martin & Wilsey ; Jackson et al ; Kohl et al ), and cattle are used to facilitate establishment of native grasses and forbs in restorations (Bouressa et al ; Allred et al 2011 a ). Although very intense grazing can be detrimental to species diversity, moderate grazing (either in frequency or intensity) could have positive effects on species diversity when the grazing mammals feed on dominant grasses and sedges, especially when grazing is patchy (Allred et al 2011 b ).…”
Section: Introductionmentioning
confidence: 99%
“…Although previous work found bison and cattle grazing sites were 85% similar in plant community, the observed small scale differences in plant richness and diversity (Towne et al 2005) could significantly affect bees that have low mobility. Bison grazing can help increase rare plant species (Wilsey and Martin 2015), as well as landscape level heterogeneity (McMillan et al 2011;Kohl et al 2013), which could be important to bee diversity. Future studies should investigate differences in bison and cattle grazing on bee diversity mediated by differences in plant diversity.…”
Section: Grazingmentioning
confidence: 99%
“…How well this can mimic historic natural conditions is unclear. In studies that compared bison and cattle, bison consumed a higher proportion of grasses and sedges relative to forbs and woody vegetation, exhibited much larger foraging patches, and spent less time in wooded areas and near water while foraging, among other differences (Knapp et al 1999, Allred et al 2011, Kohl et al 2013. Although one smallscale (4.9 ha pastures) study in tallgrass prairie found that differences between bison and cattle foraging had minor effects on plant communities (Towne et al 2005), longterm effects may be substantial at larger scales where animals can interact with complex landscapes (Allred et al 2011, Kohl et al 2013.…”
Section: Bcm Approach: Manage For Grazing Heterogeneity and Multi-scamentioning
confidence: 99%
“…Fluctuation in stream flows and the availability of water also strongly influence grazing patterns; scarce water sources can be expected to create more variable grazing conditions across the landscape as animals must travel further between water and grazing sites (Allred et al 2011). Bison readily forage more than 10 km from water-possibly much more-and thus, in contrast to cattle, are well adapted to water scarcity (Kohl et al 2013).…”
Section: Bcm Approach: Manage For Natural Stream Flowsmentioning
confidence: 99%